Determinants of the energy cost of front-crawl swimming in children - Poujade, B.; Hautier, C. A.; Rouard, A. (European Journal of Applied Physiology, 2002)
The aim of the present study was to define the determinants of the energy cost of swimming (Cs) in children. Eleven healthy children [mean (SD) age: 12.42 (0.53) years] who practised 7.5-8.5 h·week-1 volunteered to take part in this study. Anthropometric dimensions such as height (H), body mass (BM), hydrostatic lift (HL) and body surface area (SA) were measured. Forty-eight hours later when maximal oxygen consumption (VO2max) had been measured during 400 m of front-crawl swimming, Cs was measured over 200 m for three submaximal swimming speeds (0.9, 1.0 and 1.1 m·s-1). Oxygen consumption (Douglas bag method), stroke frequency (SF) and stroke length (SL) were calculated during the last 50 m of each 200 m. The mean (SD) VO2max of the young swimmers was 2.19 (0.38) l·min-1 at a maximal aerobic velocity of 1.19 (0.03) m·s-1. The values of VO2 for Cs at 0.9 m·s-1, 1.0 m·s-1 and 1.1 m·s-1 were 29.27 (3.13) ml·m-1, 30.25 (3.68) ml·m-1 and 32.91 (3.59) ml·m-1, respectively. There was a significant increase in Cs with increasing swim speed. In addition, SF increased with velocity when SL remained constant. The values for SF at 0.9 m·s-1, 1.0 m·s-1 and 1.1 m·s-1 were 31.28 (4.36) strokes·min-1, 34.10 (5.09) strokes·min-1 and 38.31 (5.90) strokes·min-1, respectively. No significant correlation was obtained between Cs and the anthropometric or stroking parameters. It was concluded that for young swimmers, anthropometric characteristics, SF and SL are not good predictors of Cs in front-crawl swimming, and that further studies are needed to explore the influence of underwater torque on Cs in prepubertal children.